Anteroposterior location of the mandibular foramen of 7 to 12 year-old children in panoramic radiographs - Evelise Ono; Edmundo Médice Filho; Luiz C. de Moraes; Julio C. de M. Castilho; Maria Eli L. de Moraes (Brazilian Dental Science)
The mandibular foramen (MF) location is considerably important in dentistry practice. It determines the success of anesthesia procedures on the mandibular structures. Many researches about its location in adults can be found in the literature; however the results are not always in agreement. The aim of this study was to evaluate the anteroposterior position of the MF, and verify the possible changes on its location on 7 to 12 year-old children. Ninety panoramic radiographs from the Dentomaxillofacial Radiology department at the Dentistry School of São José dos Campos - São Paulo State University - were examined. The shortest anteroposterior length of the mandibular ramus and the distance between the point correspondent to the MF to the deepest portion of the anterior border of the mandibular ramus were obtained using a digital caliper. All the measurements were registered in millimeters. The ratio between the measurements was calculated. The descriptive statistic analysis and the 95% confidence interval ANOVA (one-way) test were applied. The results showed that the anteroposterior location of the MF is, on average, at the medium third of the mandibular ramus. No statistically significant differences were found between ages (p>0.05).